Indirect calorimetry can be used to measure cardiac output in septic patients? - Martins,Maria Auxiliadora (2008)
PURPOSE: The aim of this study was to compare two different cardiac output (CO) monitoring systems based on the thermodilution principle (Thermo-CO) and indirect calorimetry (Fick mixed-CO) in septic patients. METHODS: Prospective study in septic patients admitted in an intensive care unit of a university hospital. Nineteen patients aged on average 45.4 ± 21.5 years were enrolled in the study. Four series of hourly measurements by the two techniques were carried out simultaneously. RESULTS: No significant differences were observed between Thermo-CO and Fick mixed-CO (7.0 ± 1.8 L.min-1 and 6.4 ± 1.7 L.min-1.). Parallel analysis of Fick mixed-CO and Fick atrial-CO was performed introducing a correction factor for the eight atrial samples in order to adjust the values of oxygen saturation obtained from atrial blood (Fick corrected atrial-CO) to those obtained from mixed venous blood. No significant differences could be detected between Fick mixed-CO and Fick corrected atrial-CO. The correlation coefficients of Thermo CO/Fick mixed-CO and Fick mixed-CO/Fick corrected atrial-CO were 0.84 and 0.94, respectively. CONCLUSION: We observed that the agreement between the two methods was satisfactory on the basis of the decisions made for treatment. Indirect calorimetry is useful to measure CO in patients with septic shock.